Cinta Yang Terbatas : Telaah Qs. Albaqarah 221 Tentang Cinta Nikah Beda Agama - Muhammad Baihaqi; Edi Hermanto (CV. ITTC INDONESIA, 2025)
Interfaith relationships among the younger generation are increasingly seen as a social phenomenon considered normal amidst digital culture, social media, and modern narratives of tolerance. Love is positioned as a personal right that is often considered free from religious boundaries. This study aims to examine the concept of